Operational Evaluation of the Effectiveness of Long-lasting Insecticidal Nets on Human-Vector Contact in an African Urban Malaria Context. (30th December 2020) - Traoré, Dipomin F; Sagna, André B; Assi, Serge B; Tchiekoi, Bertin N'Cho; Adja, Akré M; Dagnogo, Mamadou; Koffi, Alphonsine A; Rogier, Christophe; Remoue, Franck
Abstract: Background: Malaria is still a major public health concern in Côte d'Ivoire despite mass distribution of long-lasting insecticidal nets (LLINs) as a key preventive strategy. This study intended to evaluate the operational effectiveness of LLINs on the level of human-vector contact using 1 antibody-based biomarker of exposure to Anopheles in urban areas. Methods: This cross-sectional study collected socio-demographic data and use of LLINs from 9 neighborhoods in the city of Bouaké (Côte d'Ivoire). Dry blood spots performed in children aged >6 months and adults were used to evaluate immunoglobulin G (IgG) responses to the Anopheles gSG6-P1 salivary peptide. Results: IgG response levels to the salivary peptide were significantly lower in individuals who declared having "always" (n = 270) slept under an LLIN compared with those who had "often" (n = 2087) and "never" (n = 88) slept under an LLIN ( P < .0001). IgG response levels to gSG6-P1 between those who declared having "always" and "not always" slept under an LLIN varied according to neighborhood, socio-professional category, and age group. Conclusions: The human IgG level to this gSG6-P1 salivary peptide could be a useful tool to evaluate the actual effectiveness of LLINs and help design behavioral change interventions that are crucial for sustaining universal coverage.